Settlement of Santet Crimes through Criminology in the Perspective of Criminal Law - Charisma Ledhi Fitriani; Arief Syahrul Alam (Budapest International Research and Critics University, 2023)
Santet is an act of harming others by using magic. Indonesian people sometimes often commit criminal acts or take the law into their own hands against someone who is accused of being a perpetrator of Santet, either in the form of minor abuse, serious abuse, beatings, and even murder. The purpose of this study was to find out the settlement of Santet crimes from a criminological perspective and Santet crimes from a criminal law perspective. The type of research used is normative legal research using statutory and conceptual approaches. The results of the study show that from a normative legal perspective, Santet is a crime that can be accounted for by looking at the criminology and criminal law perspectives committed by people who deliberately announce themselves as having supernatural powers and can be used as criminal offenses as stipulated in the Criminal Code. (KUHP) of 2019 concerning the criminalization of Santet Article 252. Whereas the object of criminology is a person in conflict with social norms, while the object of criminal law is a violation of law and order. The formulation of the crime of Santet in the Criminal Code is a formal offense, which means that if all the elements have been fulfilled then criminal sanctions can be imposed regardless of the consequences of their actions. So, the process of proving the meaning of Santet that is proven is not the Santet but the relationship between the Santet and the person who hired her so that that relationship will be seen as a crime. Because our country is a country of law, there must be a law that protects its people even if the people are proven guilty and still carry out the punishment following what was violated.